Implementation of Lecturer's Professional Competency in Assessing Financial Performance - Agus Eko Sujianto (STAI Miftahul Ula Nganjuk, 2021)
This research is intended to implement the lecturer's professional competence, especially in assessing the performance of Puskesmas from the aspect of current ratio, efficiency ratio, and ROA. The research approach chosen is quantitative with descriptive research. The data collection technique uses documentation, namely financial reports published by Puskesmas